Accuracy of measurements performed on digital panoramic radiographs with and without an extra-oral calibration object - Ivanović, Anita (Array, 2020)
To investigate the accuracy of measurements in vertical and horizontal direction using an extra-oral calibration object placed in different positions on the panoramic radiograph in JPEG and DICOM image format. Methods: Digital panoramic radiographs of a purpose made model with 32 removable teeth replaced with metal balls were taken. The measurements of metal balls were performed with and without the calibration object placed in the middle or on the side of the radiograph in JPEG and DICOM image formats. Results: One sample t-test was used for the analyses of accuracy of measurements in vertical and horizontal direction. The most accurate vertical measurements were achieved in canine group in JPEG (6.02±0.04 mm, P=0.144) and DICOM (6.03±0.07 mm, P=0.104) formats using calibration object placed in the middle of the radiograph. The mean values of measurements in horizontal direction differed significantly from the real values (P<0.05) in all teeth groups regardless of the image format. Conclusion: The most accurate measurements in vertical direction were achieved by placing the metal scale ruler extra-orally in the middle of panoramic radiograph independent of the image format. Reliable clinical accuracy for measurements in horizontal direction was achieved only in canine region (G2) in both image formats.